Anxiety, concerns and COVID-19: Cross-country perspectives from families and individuals with neurodevelopmental conditions - Sideropoulos, Vassilis; Van Herwegen, Jo; Meuleman, Ben; Alessandri, Michael; Alnemary, Faisal M; Rad, Jamal Amani; Lavenex, Pamela A Banta; Bolshakov, Nikita; Bölte, Sven; Buffle, Paulina; Cai, Ru Y; Campos, Ruth; et al. (International Society of Global Health, 2023)
Background The COVID-19 pandemic had a major impact on the mental health and well-being of children with neurodevelopmental conditions (NDCs) and of their families worldwide. However, there is insufficient evidence to understand how different factors (e.g., individual, family, country, children) have impacted on anxiety levels of families and their children with NDCs developed over time. Methods We used data from a global survey assessing the experience of 8043 families and their children with NDCs (mean of age (m) = 13.18 years, 37% female) and their typically developing siblings (m = 12.9 years, 45% female) in combination with data from the European Centre for Disease Prevention and Control, the University of Oxford, and the Central Intelligence Agency (CIA) World Factbook, to create a multilevel data set. Using stepwise multilevel modelling, we generated child-, family and country-related factors that may have contributed to the anxiety levels of children with NDCs, their siblings if they had any, and their parents. All data were reported by parents. Results Our results suggest that parental anxiety was best explained by family-related factors such as concerns about COVID-19 and illness. Children’s anxiety was best explained by child-related factors such as children’s concerns about loss of routine, family conflict, and safety in general, as well as concerns about COVID-19. In addition, anxiety levels were linked to the presence of pre-existing anxiety conditions for both children with NDCs and their parents.Conclusions The present study shows that across the globe there was a raise in anxiety levels for both parents and their children with NDCs because of COVID-19 and that country-level factors had little or no impact on explaining differences in this increase, once family and child factors were considered. Our findings also highlight that certain groups of children with NDCs were at higher risk for anxiety than others and had specific concerns. Together, these results show that anxiety of families and their children with NDCs during the COVID-19 pandemic were predicted by very specific concerns and worries which inform the development of future toolkits and policy. Future studies should investigate how country factors can play a protective role during future crises.